Bioprospecção de extratos e/ou substâncias frente à células de melanoma e patógenos humanos - Silva, Paulo Henrique Freitas da (2017)
Today, at least 75 species of Talaromyces are known, and due to this number of species the interest in chemical and biotechnological studies has increased. The main secondary metabolites produced by individuals of this genus are derived from alkaloids, peptides and mainly polyketides. Therefore, the present study had the objective of bioprospecting extracts and / or molecules produced by the fungus Talaromyces sp. (DgCr22.1b) an endophyte isolated from Duguetia stelachantha against melanomic cells and human pathogens. The fungus was cultivated in ISP2 medium for 28 days under a temperature of 28 ° C. After cultivation, the crude extract was obtained which was then fractionated on a silica gel column using gradient elution. After chromatographic analysis, fraction 03 presented characteristics compatible with polyketides (retention factor and development color). This fraction was subjected to preparative CCD leading to the isolation of a pure substance. After analysis by NMR and MS it was possible to identify the isolated substance as paecilin D. It is concluded that the isolated substance presents activity in different concentrations against the human pathogens Candida albicans and tropicalis, already against the melanomic cells this molecule did not present necessary cytotoxic activity For the evaluation of IC50 Key words: Biotechnology, polyketide, nuclear magnetic resonance, Talaromyces, paecilin D, xanthones.